Emerging toolset of three-dimensional pulmonary cell culture models for simulating lung pathophysiology towards mechanistic elucidation and therapeutic treatment of SARS-COV-2 infection - Ni, Kai; Che, Bo; Yang, Chongxin; Qin, Youyuan; Gu, Rong; Wang, Chunhong; Luo, Mingzhi; Deng, Linhong (Frontiers in Pharmacology, 2022)
The ongoing COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) poses a never before seen challenge to human health and the world economy. However, it is difficult to widely use conventional animal and cell culture models in understanding the underlying pathological mechanisms of COVID-19, which in turn hinders the development of relevant therapeutic treatments, including drugs. To overcome this challenge, various three-dimensional (3D) pulmonary cell culture models such as organoids are emerging as an innovative toolset for simulating the pathophysiology occurring in the respiratory system, including bronchial airways, alveoli, capillary network, and pulmonary interstitium, which provide a robust and powerful platform for studying the process and underlying mechanisms of SARS-CoV-2 infection among the potential primary targets in the lung. This review introduces the key features of some of these recently developed tools, including organoid, lung-on-a-chip, and 3D bioprinting, which can recapitulate different structural compartments of the lung and lung function, in particular, accurately resembling the human-relevant pathophysiology of SARS-CoV-2 infection in vivo. In addition, the recent progress in developing organoids for alveolar and airway disease modeling and their applications for discovering drugs against SARS-CoV-2 infection are highlighted. These innovative 3D cell culture models together may hold the promise to fully understand the pathogenesis and eventually eradicate the pandemic of COVID-19.